The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1111/j.1477-9552.1992.tb00239.x
|View full text |Cite
|
Sign up to set email alerts
|

Contingent Valuation for Household Water in Rural Ghana

Abstract: This study uses an iterative bidding approach to examine the relationship between selected socioeconomic characteristics of households and their willingness to pay for water. The study uses survey data from selected villages in Ghana. The results show that household income is the principal factor influencing the willingness to pay for water. There was a statistically significant positive relationship between households' history of water‐related illness and their willingness to pay for water. The effect of most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…There have been relatively few published studies on contingent valuation in developing countries. Those that exist have focused on the demand in poor countries for education (Thobani, 1983;Mingat and Tan, 1986;Jimenez, 1987), health services (Jimenez, 1987), sanitation services (Whittington , Lauria and Wright, 1993;Altaf and Hughes, 1994), and rural water supplies (Boadu, 1992;Singh et al, 1993;Altaf et al, 1993;Bohm, Essenburg, and Fox, 1993). In addition, the World Bank initiated a multicountry study of the willingness-to-pay for potable water in 1987, which resulted in several contingent valuation analyses (Whittington et al, 1990(Whittington et al, , 1991Briscoe et al, 1990;Griffen et al, 1995).…”
Section: Comparison With Similar Studiesmentioning
confidence: 99%
“…There have been relatively few published studies on contingent valuation in developing countries. Those that exist have focused on the demand in poor countries for education (Thobani, 1983;Mingat and Tan, 1986;Jimenez, 1987), health services (Jimenez, 1987), sanitation services (Whittington , Lauria and Wright, 1993;Altaf and Hughes, 1994), and rural water supplies (Boadu, 1992;Singh et al, 1993;Altaf et al, 1993;Bohm, Essenburg, and Fox, 1993). In addition, the World Bank initiated a multicountry study of the willingness-to-pay for potable water in 1987, which resulted in several contingent valuation analyses (Whittington et al, 1990(Whittington et al, , 1991Briscoe et al, 1990;Griffen et al, 1995).…”
Section: Comparison With Similar Studiesmentioning
confidence: 99%
“…The researchers concluded that households' WTP for water system is not dependent on anyone set of factors but rather on their joint effects and on specific cultural setting. Boadu [8] examined the relationship between WTP for water and selected socioeconomic characteristics using data from selected villages in Ghana and obtained a positive relationship between household history of water related illness and the WTP for water services. The other socioeconomic factors effect did not follow any consistent pattern and therefore broad generalisations were not possible.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It has been argued that older people care more about future generations or that they are more conscious about health issues, implying a positive impact of age on the WTP (Muhammad et al, 2015;Brouwer et al, 2016). Others argue that younger people are more conscious about environmental issues, implying a negative impact on the WTP (Boadu, 1992; terms of use, available at https://www.cambridge.org/core/terms. https://doi.org/10.1017/S1355770X16000255 Belluzzo, 2004;O'Garra and Mourato, 2006;Shultz and Soliz, 2007;Alpízar and Madrigal, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…https://doi.org/10.1017/S1355770X16000255 Belluzzo, 2004;O'Garra and Mourato, 2006;Shultz and Soliz, 2007;Alpízar and Madrigal, 2016). Similarly, some authors suggest that the higher the household's size the lower the WTP, since there are more competitive uses for the family income (Boadu, 1992;Amponin et al, 2007). Nevertheless, others authors argue that the presence of children at home would increase the WTP (Shultz and Soliz, 2007).…”
Section: Resultsmentioning
confidence: 99%